(untitled) (International journal of artificial intelligence, 2025)
This article explores effective methodological approaches to help students of foreign language universities avoid common grammar mistakes in the IELTS exam. It highlights the significance of understanding grammatical accuracy, applying structured learning techniques, and utilizing high-quality resources. The article discusses key strategies for improving grammar in writing and speaking sections, along with common errors students make. Additionally, it offers practical solutions to overcome grammatical challenges and maximize IELTS scores.